High Porosity Mn-Zn Ferrites Obtained by Using Mechano-Chemical and Wet Chemical Method - J. Pissurlekar, Vikas; S. Budkuley, Jayant (Asian Journal of Chemistry, 2010)
Manganese-zinc ferrites are synthesized by two different methods namely mechano-chemical and wet chemical, using same ligand. XRD data is used to confirm formation of single phase of ferrites. Lattice constants, X-ray densities, mass densities of the ferrite samples are determined. Porosities calculated by densities method for the samples are found to have high values.